All my bicycles - Power Paola (Fantagraphics Books, Inc., 2024)
"“A bicycle is a machine that you power yourself. You decide where you want to go,” writes cartoonist Powerpaola, as the guiding principle of this graphic memoir. All My Bicycles is a story that never really begins, existing all at once in Paola’s memory. The book illustrates Powerpaola’s relationships through her many bicycles: in fragments, it takes her back to her great loves and losses, friendships, and disappointments. In remembering a bicycle, a manhole, an alligator, or a necklace, Powerpaola reflects upon these items in her consciousness without finding a concrete solution. Paola’s memories arrive abruptly and leave just as fast, creating a pathway through herself she can only find in moving forward. All My Bicycles is a glimpse into how exploring these fleeting tangible moments ― of physical objects, of traveling and seeing a new city, of even the end of a relationship ― is an exploration of self."--Amazon